Monolithic nanoscale photonics-electronics integration in silicon and other group IV elements - Radamson, Henry H.; Thylén, Lars (Academic Press, 2014)
Silicon technology is evolving rapidly, particularly in board-to-board or chip-to chip applications. Increasingly, the electronic parts of silicon technology will carry out the data processing, while the photonic parts take care of the data communication. For the first time, this book describes the merging of photonics and electronics in silicon and other group IV elements. It presents the challenges, the limitations, and the upcoming possibilities of these developments. The book describes the evolution of CMOS integrated electronics, status and development, and the fundamentals of silicon p.